2019
DOI: 10.1113/jp278024
|View full text |Cite
|
Sign up to set email alerts
|

Endocytic recycling of Na+–K+–Cl cotransporter type 2: importance of exon 4

Abstract: Key points Na+–K+–Cl− cotransporter type 2 (NKCC2) is a 27‐exon membrane protein that is expressed in the thick ascending limb (TAL) of Henle where it is involved in reabsorption of the ultrafiltered NaCl load. It comes as three splice variants that are identical to each other except for the residue composition of exon 4 and that differ in their transport characteristics, functional roles and distributions along the TAL. In this report, it is shown that the variants also differ in their trafficking properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 68 publications
(129 reference statements)
0
4
0
Order By: Relevance
“…In simulation analyses Chew et al further showed that the CL1 domain of one monomer could interact with the C-terminus of the opposite monomer. This finding was of special interest in view of the role that the TMD2-CL1 domain of NKCC2 was found to play (Gagnon et al, 2004(Gagnon et al, , 2005(Gagnon et al, , 2002Gimenez et al, 2002;Marcoux et al, 2019aMarcoux et al, , 2019bPlata et al, 2002). Similar analyses also showed that the ion-binding sites were contained within a solvent-accessible vestibule that was delineated by TMD1, TMD3, TMD6, and TMD8.…”
Section: Structure Of Nkcc2mentioning
confidence: 63%
See 2 more Smart Citations
“…In simulation analyses Chew et al further showed that the CL1 domain of one monomer could interact with the C-terminus of the opposite monomer. This finding was of special interest in view of the role that the TMD2-CL1 domain of NKCC2 was found to play (Gagnon et al, 2004(Gagnon et al, , 2005(Gagnon et al, , 2002Gimenez et al, 2002;Marcoux et al, 2019aMarcoux et al, , 2019bPlata et al, 2002). Similar analyses also showed that the ion-binding sites were contained within a solvent-accessible vestibule that was delineated by TMD1, TMD3, TMD6, and TMD8.…”
Section: Structure Of Nkcc2mentioning
confidence: 63%
“…The apparent ion affinity (K m ) and maximal transport capacity (V max ) of the NKCC2 splice variants have been determined by at least three research groups in the oocyte expression system (Gimenez et al, 2002;Marcoux et al, 2019aMarcoux et al, , 2019bPlata, Meade, Vazquez, Hebert, & Gamba, 2002). Among the experiments carried out by these research groups, the NKCC2 analyzed were not all from the same species and the conditions used differed to some degree.…”
Section: Kinetics Of Ion Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…Rb + flux assays Synthetic genes for KCC1 and KCC3 variants with N-terminal HAtag were cloned into pPOL vector for in vitro transcription (Marcoux et al, 2019). Defolliculated stage V-VI Xenopus laevis oocytes were microinjected with 50 ng cRNA and maintained in Barth medium for 3 days at 18°C in the presence of 1.5 mM furosemide.…”
Section: Cryo-electron Microscopy Sample Preparation Data Collection ...mentioning
confidence: 99%